Mercy Watson : something wonky this way comes - DiCamillo, Kate.; Van Dusen, Chris (Somerville, MA : Candlewick Press, 2009)
Mr. and Mrs. Watson think it is a wonderful idea to bring their pet pig Mercy to the drive-in, and when Mercy arrives, she sets off on a mission to find her own buttery bucket of popcorn, much to the dismay of the other movie patrons.
School Library Journal, August 2009.
Horn Book, April 2010.
3.1
K-3
530L
L
Keywords: Watson, Mercy (Fictitious character) -- Juvenile fiction; Swine as pets -- Juvenile fiction; Watson, Mercy (Fictitious character) -- Fiction; Pigs -- Fiction; Pets -- Fiction; Drive-in theaters -- Fiction; Pigs -- Fiction; Pets -- Fiction; Drive-in theaters -- Fiction; Humorous fiction; Pigs -- Fiction; Humorous stories; Humorous fiction